Towards instantaneous quantitative fluoroimaging drugs determination in body fluids with no added reagents. Issue 3 (2010) - Strashnikova, Natalia V.; Gershanik, Arcady P.; Papiashvili, Nona; Khankin, Daniel; Cohen-Luria, Rivka; Mark, Shlomo; Kalisky, Yehoshua; Parola, Abraham H.
Abstract : Our objective is to develop a simple monitoring technique for rapid, sensitive and quantitative drugs detection in body fluids, with no reagent added and no need for qualified professionals. The user-friendly automatic Fluo-imager will (a) measure the full-range 3D fluorescence map of the inserted fluid sample, (b) determine the chemical nature and concentration of the drugs and (c) transfer the results through internet to the diagnosis center. For these goals the fluorescence measurement data will be examined by neuronal network-pattern recognition software. The software identifies the chemical nature and the appropriate concentration of the drug by comparison of the obtained 3D pattern with the contents of the data bank. One of the problems in the approach under consideration is the high optical density of body fluids in the UV region, which raises difficulties in the fluorescence measurements. In this paper, we have attempted to overcome this problem by means of preliminary dilution. Nevertheless, the problem of subtraction of the fluid fluorescence background still needs to be addressed.